Answers

Well basically I think the simplest way to do this is to make yourself a couple of simultaneous equations so given that f(-3) = 0 and f(4) =21 you can make the following two equations:
0=18-3p+q which also equals:
18= 3p -q (1)
and
21= 32+4p +q which also equals:
-11 = 4p +q (2)
If we add equations (1) and (2) together then we can eliminate the q from both equations giving us:
7p=7 so p=1
Then putting p=1 back into either equation (1) or (2) we find that q=-15

20 January 2011

Add an answer Cancel reply

Similar questions